BIOLOGICAL EVALUATION OF 2-ARYLIDENE-4-(METHOXYPHENYL)BUT-3-EN-4-OLIDES - Asif Husain4*Mohammad Maaz1, Aftab Ahmad2, Shah Alam Khan3 (Journal of Biomedical and Pharmaceutical Research, 2017)
A series of 2-Arylidene-4-(methoxyphenyl)but-3-en-4-olides were screened against Pheretima posthuma earthworm for anthelmintic activity. The in vitro effects of compounds were evaluated at a concentration of 2mg/mL and time taken by the compounds to paralyze and subsequently kill the worms was recorded. Butyrolactone derivatives exhibited moderate to good anthelmintic activity but among all tested compounds, compound II, 2-(3,4,5-trimethoxy-benzylidene)-4-(methoxyphenyl)but-3-en-4-olide, was found to be the most potent against Pheretima posthuma. The anthelmintic activity of compound II was observed to be comparable with positive control albendazole in terms of paralytic and lethal time. Keywords: Furnaone, Butyrolactone, Pheretima posthuma, Anthelmintic.